RF shield parallel-plate waveguide for travelling-wave MRI experiments at 3 T. (June 2019) - Marrufo, O.; Vazquez, F.; Martin, R.; Solis-Najera, S. E.; Rodriguez, A. O.
Abstract: Ultra high field magnetic resonance imaging systems suffer from the standing wave problems produced by conventional radiofrequency coils. This causes inhomogeneous fields degrading the image quality. To overcome this problems, propagation of RF waves by antennas inside a waveguide is suggested. We assessed the feasibility of using the magnet RF shield with aluminium strips to form a parallel-plate waveguide for travelling-wave magnetic resonance imaging at 3 T. Imaging results showed that a number of constraints must be solved before good image quality can be obtained. A brief discussion is presented on the possible sources or error and interference. Despite these limitations, results are really encouraging to continue investigating the implementation of this approach.